2018
DOI: 10.3168/jds.2018-14736
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci and putative causal variants affecting somatic cell score in dairy sheep by using a 50K SNP chip and whole-genome sequencing

Abstract: This study presents a scan of the ovine genome to identify quantitative trait loci (QTL) influencing the somatic cell score (SCS), a classical indicator of subclinical mastitis in sheep, and a subsequent high-resolution analysis of one of the identified QTL regions based on the analysis of whole-genome sequence data sets. A half-sib commercial population of Churra sheep genotyped with a 50K SNP chip was analyzed using linkage analysis (LA) and combined linkage and linkage disequilibrium analysis (LDLA). By LA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Moreover, whole-genome re-sequencing of target animals has been used to restrict the number of candidate polymorphisms. Thus, putative causative mutations that affect traits of economic interest have been proposed [2124].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whole-genome re-sequencing of target animals has been used to restrict the number of candidate polymorphisms. Thus, putative causative mutations that affect traits of economic interest have been proposed [2124].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the genetic variability of the studied animals was carried out by considering the six resistant and six susceptible sheep as a single group, as it has been shown that a higher number of samples considered during variant calling analysis results in a higher coverage and confidence in variant calls (Piskol et al ). To ensure the quality of the variants identified, we performed the variant calling analysis with two different software packages, gatk and Samtools , such as in Gutiérrez‐Gil et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Both Lacaune and Manech Tête Rousse populations were genotyped with a 960 custom-designed ovine SNP chip [10]. The chip was designed and developed within the 3SR EU project [3] based on several QTL for SCC that were previously identified in Spanish Churra [11], French Lacaune [4] and Italian Sardinian–Lacaune backcross populations ([12] and personal communication). Using these previous association studies, seven regions of interest (Table 3) on Ovis aries (OAR) chromosomes 2, 3, 5, 16 and 18 were selected based on commonalities among populations found at the time (in 2012) or on their high significance.…”
Section: Methodsmentioning
confidence: 99%